Ces femmes qui ont bâti Montréal : la petite et grande histoire des femmes qui ont marqué la vie de Montréal depuis 350 ans - Darsigny, Maryse; Descarries, Francine; Kurtzman, Lyne; Tardy, Évelyne (Les éditions du remue-ménage, 1994)
Plus de 350 chroniques et illustrations, couvrant l’histoire de Montréal depuis sa fondation, répertoriant des réalisations dans tous les secteurs d’activités, des synthèses et des repères chronologiques précieux sous la plume alerte de plus de 150 collaboratrices: journalistes, historiennes, militantes féministes, chercheures, étudiantes, écrivaines…
Keywords: SAC; amériques; discipline; histoire; histoire des femmes*; histoire et politique; montréal; politique; québec; régions géographiques; sciences humaines; thématiques

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail